Identity and change in East Asian conflicts : the cases of China, Taiwan, and the Koreas - Horowitz, Shale Asher; Heo, Uk, 1962-; Tan, Alexander C. (Palgrave Macmillan, 2007)
Changing national identities have transformed the China-Taiwan and Korean conflicts. Democratization in Taiwan and South Korea, and liberalization in China, have forced leaders to compete for popular legitimacy by appealing to national identities. Along with the collapse of the Soviet Union, these contested national identities have been the main factors driving change in the conflicts?pushing China and Taiwan inexorably apart and toward a showdown, while helping to prop up what appeared to be a mortally wounded North Korea. This explains why one U.S. ally, Taiwan, becomes more hawkish, while the other, South Korea, becomes more dovish. U.S. foreign policy is struggling to adjust.